052: BARRIERS TO HEALTH RESEARCH USE IN KENYA AND MALAWI. (24th August 2015) - Oronje, Rose N; Murunga, Violet I; Longwe-Ngwirai, Abiba L; Mushani, Nissily M; Abisi, Jones A; Zulu, Eliya M
Abstract : Background: Application of research evidence in policies and programmes in order to improve service delivery is equally as important as its generation. An important determinant of research application in health policies and programmes is the technical and institutional capacity of ministries of health (MoH) in applying research evidence. Objectives: This paper highlights important barriers to research use within the MoH in Kenya and Malawi. Methods: Data collection involved document review, key informant interviews, focus group discussions, and consultations with senior MoH officials. Result: The emergent barriers to research use were categorized as access, institutional and individual barriers. Access barriers included: lack of a national health research repository that would consolidate all health research; lack of journal subscriptions, poor packaging and dissemination of research; limited availability of operational research and research in highly specialized fields; and weak links with researchers. Institutional barriers included: limited funding to health research; inadequate staffing; lack of research use guidelines, supportive infrastructure, incentives for research use, institutional forums for deliberating new research, and research use culture; weak institutional leadership for evidence use; weak institutional linkages between the MoH and research institutions; senior policymakers' suspicion of using research funded by donor agencies; and political interests. Individual barriers included lack of technical skills required to enable research use, competing demands on staff-time, lack of knowledge of free journal databases, and limited appreciation of the importance of research use among senior MoH officials. Conclusion: Findings suggest that efforts to enable increased use of research evidence in health policymaking and programming should also address demand-side barriers to research application, i.e. factors that hinder MoH policymakers and technical staff from searching, appraising, synthesizing and applying research evidence.